Dream drawings : configurations of a timeless kind - Momaday, N. Scott, 1934- (Harper Perennial, 2022)
"From Pulitzer Prize winner and celebrated American master N. Scott Momaday, a collection of 100 new prose poems, rooted in Native American oral tradition, along with 5-7 pieces of art by the author"--